Features of the Epidemic Process of Viral Hepatitis A and E in the Russian Federation - A. N. Kaira; O. A. Svitich (Эпидемиология и вакцинопрофилактика)
Relevance. In the Russian Federation, in recent decades, there has been a decrease in the incidence of hepatitis A (HA), at the same time, not only sporadic morbidity is registered, but also an outbreak. A decrease in the circulation of the HA virus affected the increase in the number of people without antibodies to the virus, which led to a shift in the incidence to older age groups and an increase in more severe forms of the disease. Hepatitis E (HE) is quite widespread in the world, and its specific weight in the structure of acute viral hepatitis in some countries reaches 50.0%. HE has been registered in the Russian Federation only since 2013. only in certain territories, and the incidence rates are very low. In all likelihood, this indicates a hidden circulation of the HE virus in the Russian Federation. To understand the current epidemiological situation in the incidence of HA and HE, it is necessary to understand the current trends in the epidemic process of these infections. The purpose of this work was to compile an epidemiological characteristic of the incidence of hepatitis A and E in the population of the Russian Federation at the present stage for the formation of proposals for improving the system of preventive and anti-epidemic measures.Materials and methods. To achieve this goal, a retrospective epidemiological analysis of the incidence of viral hepatitis A and E in the territory of the Russian Federation, including in federal districts, was carried out. The materials for the study were the forms of official statistical observation No. 2, 5, 6 and 23, as well as state reports «On the state of sanitary and epidemiological well-being» in the Russian Federation region for 2011–2020.Results. The conducted research allows us to compare the epidemic process of hepatitis A and E in the Russian Federation with other regions of the world. The intensity of the epidemic process of HA has significantly decreased, at the same time, there is an uneven distribution of morbidity in various federal districts. In the age structure of patients with HA, the highest incidence rates are observed among the child population and adolescents. The frequency of HA infection and a decrease in the specific weight in the structure of acute viral hepatitis were revealed. Although the territory of the Russian Federation is not endemic for hepatitis E, this disease has taken root completely. The incidence of hepatitis E in the Russian Federation is at a sporadic level. The highest incidence of HE in the Russian Federation was observed among the adult population aged 18 years and older. The issue of carrying out preventive measures, including vaccination, remains relevant.Conclusion. On the territory of the Russian Federation, there is currently a steady trend of reducing the incidence of hepatitis A. However, children under the age of 14, adolescents, as well as nonimmune adults, among whom cases of diseases are registered, are still at risk. This requires adjusting the methods of preventing this infection, which is possible not only by improving sanitary and communal improvements, but also by vaccination within the national vaccination calendar, and not only for epidemic indications. The true incidence of HE today is obviously much higher than that recorded in official statistical forms, and this requires the introduction into clinical practice (especially at the polyclinic level) of modern available tests for detecting markers of the hepatitis E virus when examining patients with symptoms of liver damage, as well as the development of effective prevention methods.